Pemahaman Kesetaraan Gender Dalam Keluarga Untuk Mewujudkan Perempuan Berdaya - Zhafarina, Adlia Nur; Silvia Diah Puspitaningrum; Fauzul Hadi Aria Langga; Reni Kartika (The Journal of Innovation in Community Empowerment, 2023)
Women and men should have an access, participation, and so on in life activities wherever they are, including in the smallest sphere, such as a family. However, women can be situated in a condition of gender inequality in the family, like a discriminatory act committed by dominant people, both structurally and culturally, for example a violence. Regarding violence, Komnas Perempuan's data show that the number of complaints received throughout 2021 was 2,527 cases of violence, which 771 cases were violence against wives and 212 cases were violence against daughters. In this case, it is important to have a program for Ibu PKK to provide an understanding related to gender equality in the family to create empowered women. The methods used in organizing this program are by giving a course, making a discussion, and giving a test regarding the course. Furthermore, the program has taken place and based on the result of the test given during the program, the participants have an average test score of 89. In this case, it can be seen that the participants' understanding of gender equality in the family to create empowered women already well. This also indicates that efforts to provide understanding to participants have been running effectively, because participants can understand the course well. Education about gender equality in the family by providing a program to Ibu PKK is very necessary because a woman has an important role in empowering a family.